Inter-household Allocations within Extended Family: Evidence from the Indonesia Family Life Survey - Firman Witoelar (Yale University, Economic Growth Center, 2005)
This paper uses data from two waves of the Indonesia Family life Survey (IFLS2-1997 and IFLS3-2000) to investigate whether households that belong to the same extended families pool their income to smooth their consumption. We exploit the fact that the survey also tracks and interviews split-off households during the follow-up surveys, enabling us to construct a panel of extended families. The findings suggest that in contradiction to the null hypothesis of extended-family income pooling, household own income still matters to household consumption even after controlling for extended family resources. The result stands after correcting for potential measurement error and endogeneity of income. More importantly, the findings also suggest that although the change in household own income matters to the change in household consumption, controlling for extended family resources, the magnitudes of the coefficients are small. We also find evidence that household consumption is affected by characteristics of other households in the same extended family.
Keywords: D13; J12; O12; 330; Consumption smoothing; risk-sharing; extended families; Verbraucherausgaben; Haushaltsökonomik; Haushaltseinkommen; Indonesien